Traffic Crash Injuries and Disabilities : The Burden on Indian Society - World Bank (World Bank, Washington, DC, 2021)
Road crashes endanger the lives and livelihoods of millions of road users globally and in India. Owing to the epidemic of road crashes, in 2010, the United Nations General Assembly proclaimed 2011 - 2020 as the "Decade of Action for Road Safety" and the Sustainable Development Goals (SDGs) included two important targets on road safety. The risk of a road crash in low-income countries is three times higher than compared to that in high-income countries. Not only does it lead to untold and unaccounted for suffering and loss for victims and their families, but also, it drains the GDP of countries by claiming millions of economically productive young lives. The World Bank estimates the total cost of Road Traffic Injuries (RTIs) at 172 billion dollars (INR 12.9 lakh crore) for the year 2016. While it is recognized that RTIs affect the developed and developing world in different ways, it also impacts poor households and disadvantaged sections of the population within developing countries differently. World Bank commissioned a survey-based assessment study in association with the Save LIFE Foundation (SLF) to determine such differential impacts more objectively in India. This study aims to capture the socioeconomic realities and nuances of road crashes at the sub-national level in India. It seeks to document inter-linkages between poverty, inequalities, road users, and road crash outcomes by analyzing data from four States in India, i.e., Uttar Pradesh, Bihar ,Tamil Nadu and Maharashtra. The four states have been selected on the basis of several criteria including demographic and geographical representation, magnitude of fatality burden and socio-economic parameters such as economic growth, poverty rate and social welfare. One state from each of the four geographical zones of the country were selected which cumulatively represents about one third of total road crash deaths in the country. In terms of economic parameters, Maharashtra and Tamil Nadu are selected to represent High Capacity States (HCS) whereas Bihar and Uttar Pradesh are selected to represent Low Capacity States (LCS).